The impact of environmental crimes and profitability on environmental disclosure in Malaysian SME sector: The role of leverage - Mohamed Adnan S.; Alahdal W.M.; Alrazi B.; Mat Husin N. (Cogent OA, 2024)
This research investigates the intricate connections between environmental crimes, profitability, leverage, and environmental disclosure in Small and Medium Enterprises (SMEs) in Malaysia from 2014 to 2019. The study adopts legitimacy theory as its theoretical lens. This study focuses on the analysis of 116 SMEs that have been convicted by the Department of Environment (DOE) in Malaysia. The data used in this analysis includes information on environmental crimes from court cases published by the DOE, as well as company and financial attributes obtained from the Companies Commission of Malaysia. Additionally, environmental disclosure metrics were collected from corporate websites. In total, there are 696 observations included in this study. The study utilizes panel data analysis to uncover the fundamental dynamics. The results of the study indicate that companies that have been convicted of wrongdoing tend to offer limited levels of environmental disclosure on their digital platforms. It is worth noting that guilty firms that are larger and more profitable tend to demonstrate increased levels of environmental disclosure. The correlation between environmental crimes and leverage has been identified as a significant factor in driving higher levels of environmental disclosure. However, the relationship between leverage, profitability, and disclosure levels did not have a similar interactive effect. The research recognizes that environmentally prosecuted enterprises face a perceived threat to their legitimacy. However, this acknowledgement is limited to a specific time frame and focuses on selected characteristics that explain differences in environmental disclosures. The information obtained necessitates a reassessment and potential improvement of existing requirements for disclosure to include provisions that prioritize sustainability, particularly within the private sector. This research contributes to the ongoing discussion on the paradox between environmental performance and transparency by focusing on a developing nations context. It offers a more nuanced understanding of legitimacy theory within the specific operational environment of SMEs. 2023 The Author(s). Published by Informa UK Limited, trading as Taylor & Francis Group.